Technodidactic model for local historical memory in students of a public secondary educational institution in Lambayeque, 2025 - Raúl, Villegas Vera, Víctor (Edelweiss Applied Science and Technology, 2026)
This study analyzed the contribution of a technodidactic model to strengthening local historical memory among students of a public secondary school in Lambayeque in 2025. The research is grounded in the conception of local historical memory as a fundamental social and cultural process for identity construction, sense of belonging, and citizenship education, which is frequently weakened by transmissive and decontextualized teaching practices. A basic quantitative approach was adopted, with a non-experimental, cross-sectional design and a descriptive–propositional scope. The population consisted of 3,500 students, from which a sample of 120 participants was selected through convenience sampling. Data were collected using the Local Historical Memory Questionnaire, comprising 20 items distributed across four dimensions, with high reliability (Cronbach’s alpha = 0.89). Data analysis was conducted using descriptive statistics in SPSS version 28. The results showed a predominance of medium levels across all dimensions of local historical memory, indicating a partial appropriation of regional narratives, practices, and identities. Identified weaknesses included limited interpretation of built heritage, low critical awareness of media influence, and insufficient intergenerational transmission of memory.